1980
DOI: 10.1128/aac.17.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ceftizoxime in animals after parenteral dosing

Abstract: The pharmacokinetic profile of ceftizoxime was studied in mice, rats, dogs, and monkeys given the drug in a single parenteral dose. The serum data after an intravenous injection were analyzed by the two-compartment open model. Cefotiam, cefmetazole, cefotaxime, and cefamandole were used as reference drugs. High concentrations of ceftizoxime were attained in the sera of all test animals and in the tissues of rats after parenteral dosing. The serum concentrations of ceftizoxime were higher than those of the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

1982
1982
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 8 publications
1
34
1
Order By: Relevance
“…Similarly, all of the PIP and PT ratios of B. fragilis in both abscess combinations were comparable although they were 4-or 30-fold higher than those of CZX. This may have been due to the higher protein binding of PIP in vivo compared to that of CZX (6,12,26) and was more apparent with the anaerobe owing to the lower MIC (high inoculum) compared to that for the Enterobacter strains. The CZX ratios of B. fragilis in the two mixed infections differed 10-fold.…”
Section: ϫ6mentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, all of the PIP and PT ratios of B. fragilis in both abscess combinations were comparable although they were 4-or 30-fold higher than those of CZX. This may have been due to the higher protein binding of PIP in vivo compared to that of CZX (6,12,26) and was more apparent with the anaerobe owing to the lower MIC (high inoculum) compared to that for the Enterobacter strains. The CZX ratios of B. fragilis in the two mixed infections differed 10-fold.…”
Section: ϫ6mentioning
confidence: 96%
“…The antibiotic dosing regimens used in this study were chosen to produce a maximum effect in this model and took into consideration the short half-life, approximately 0.2 h, of both CZX and PIP in mice (3,26). Groups of two mice were treated subcutaneously with total CZX doses of 6 to 1,536 mg/kg/day or PIP or PT doses of 24 to 6,144 mg/kg/day.…”
Section: Methodsmentioning
confidence: 99%
“…The tl/2(0) values of YM09330, presented by Komiya and colleagues (5), were 13.0 min in mice, 15.9 min in rats, 30.5 min in rabbits, 55.5 min in dogs, and 75.6 min in rhesus monkeys. Murakawa and associates (10) reported that the plasma half-lives of ceftizoxime, cefotiam, cefamandole, cefotaxime, and cefmetazole, administered intramuscularly to rhesus monkeys, were 47, 41, 34, 49, and 33 min, respectively. Thus, cefonicid showed the longest plasma half-life in mice, and ceforanide was the longest lasting cephalosporin in rats and rabbits.…”
Section: Methodsmentioning
confidence: 99%
“…In the tests with rabbits and dogs, blood samples were taken from each animal at 5, 10, 20, 30, 45, 60, 90, 120, 150, and 180 min after administration. Blood specimens from each monkey were obtained at 5,10,20,30, and 45 min and 1, 2, 3, 4, 5, and 6 h after administration. Plasma was separated from these heparinized blood samples by centrifuging at 1,400 x g at 4°C, removed by aspiration, and stored at -20°C until assayed, usually within 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…1). MICs of CPZ, CTX, and CZX for 90% of the isolates were 25, 6.25, and 6.25 pug/ml, respectively. It was reported that five strains of M. avium-intracellulare isolated from acquired immune deficiency syndrome patients were all resistant to 10 ,ug of CPZ per ml (3), coinciding with our result.…”
mentioning
confidence: 99%